Overview of new antiobesity drugs - Hainer, Vojtech (Expert opinion on pharmacotherapy, 2014)
A short overview of new drugs approved for the treatment of obesity (lorcaserin, phentermine/topiramate combination) as well as those with a perspective for approval as antiobesity drugs (cetilistat, naltrexone/bupropion combination, liraglutide) is presented. All these drugs produce significant weight loss accompanied by reductions in cardiometabolic health risks. Although the adverse events were rather rare and tended to decrease with the duration of treatment with most of these medications, the drug-specific safety concerns should be seriously considered. In order to ensure an appropriate, efficient and safe implementation of novel antiobesity drugs into the comprehensive treatment of obesity, it will be necessary to establish a network of physicians and other health-care providers well educated in obesity management.
Keywords: lorcaserin; benzazepiny; Humans; Bupropion; látky proti obezitě; liraglutid; obezita; naltrexon; hmotnostní úbytek; Phentermine; glukagonu podobný peptid 1; phentermine/topiramate; Fructose; topiramat; Weight Loss; Topiramate; Glucagon-Like Peptide 1; Liraglutide; benzoxaziny; fentermin; cetilistat; bupropion; Obesity; fixní kombinace léků; Naltrexone; lidé; Anti-Obesity Agents; Benzoxazines; fruktosa; Drug Combinations; Benzazepines; antiobesity drugs; liraglutide; naltrexone/bupropion